Fabrication and characterization of flexible supercapacitor electrodes from spent filter coffee grounds - Cevik, Umit; Aydin, Ozan; Turu, Irem Cemre; Gencten, Metin; Birol, Burak; Donmez, Koray Bahadir (SPRINGER, 2025)
The increasing demand for sustainable energy storage has driven interest in eco-friendly electrode materials with high stability and low environmental impact. In this study, activated carbon derived from coffee waste was functionalized using phosphoric and citric acids, providing a mild and green alternative to conventional strong-acid treatments. The dual-acid modification introduced oxygen and phosphorus-containing functional groups that enhanced surface wettability and electrochemical activity. The functionalized carbon was deposited onto a carbon felt substrate via electrophoretic deposition (EPD), a binder-free, uniform, and scalable coating method. Under optimized conditions, CPFAC exhibited a specific capacitance of 27.43 F g(-)1 at 10 mV s(-)1 and 29.77 F g(-)1 at 1 A g(-)1, and retained 120% of its initial capacitance after 10,000 cycles. In addition, the electrode preserved 95.9% and 83.3% of its capacitance after 1000 bending and twisting cycles, respectively, confirming excellent mechanical resilience. The mesoporous structure (2-10 nm) and improved electrolyte accessibility contributed to efficient ion transport, mechanical robustness, and stable capacitive behavior. These results demonstrate that the combination of dual mild-acid functionalization and EPD provides a green and cost-effective pathway for fabricating flexible supercapacitor electrodes with superior long-term electrochemical and mechanical stability.
Keywords: ACTIVATED CARBON; POROUS CARBON; GRAPHENE; PERFORMANCE; SURFACE; ADSORPTION; BIOWASTE; BIOMASS; SIZE; FILM; Engineering; Materials Science; Physics